Implant-Retained Partial Overdenture with Resilient Attachments - Igor Chikunov, DDS, Phuong Doan, DDS & Farhad Vahidi, DMD, MSD (Journal of Prosthodontics, 2008)
Management of partially edentulous patients can still be a prosthodontic challenge.